Preparation method of graphene reinforced copper carbide electrical contact material
By using high-energy ball milling and diffusion annealing-chemical vapor deposition technology to grow graphene in copper carbide contact materials, the problem of insufficient hardness and anti-welding capacity of existing materials is solved, and the performance improvement of the material and the possibility of large-scale production is achieved.
Patent Information
- Application Number
- CN202411908393.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-18
AI Technical Summary
The existing copper carbide contact materials have low hardness and poor anti-welding capabilities while meeting the conductivity, making it difficult to meet the high requirements of electrical appliances for contact performance.
High-energy ball mill is used to uniformly distribute the carbide reinforced phase in the copper matrix, and graphene is grown on the surface of the copper powder through diffusion annealing-chemical vapor deposition technology to form a single-layer or small-layer graphene film with few defects and complete structures.
It improves the hardness and anti-welding ability of the electrical contact material, enhances its conductive properties, is suitable for large-scale production, has a simple process, and has broad application prospects.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrical materials, and in particular relates to a method for preparing a graphene-enhanced copper carbide electrical contact material. Background Art
[0002] As the core component of the switch, the switch contact material has anti-welding performance, mechanical properties and electrical conductivity, which play a decisive role in ensuring the reliability and applicability of the switch. Carbide has the characteristics of high melting point, high hardness, and high arc starting voltage, while copper has high electrical conductivity and high thermal conductivity. The copper carbide contact material obtained by combining carbide and copper has the advantages of good conductivity, arc erosion resistance, and low cost, and is widely used in vacuum contactors and low-voltage switches. With the development of society, electrical appliances have higher and higher requirements for contact performance. On the premise of meeting the conductivity, the copper carbide contact material has the disadvantages of low hardness and poor anti-welding ability, which are gradually emerging. Graphene is composed of carbon atoms in the form of sp 2 Hybrid orbitals form a two-dimensional crystal of a single atomic layer in a hexagonal honeycomb shape. The unique structure of graphene gives it extraordinary physical properties. Ideal graphene has ultra-high strength, extremely high electrical and thermal conductivity, and is regarded as an excellent reinforcement phase for metal-based composite materials; therefore, a method for preparing a single-layer or few-layer graphene-enhanced copper carbide electrical contact material with a complete structure, few defects, and high quality, suitable for large-scale production is needed. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a method for preparing a graphene-enhanced copper carbide electrical contact material. The method is suitable for large-scale production, and the prepared electrical contact material contains a single layer or a few layers of graphene reinforcement, and has the advantages of few defects and complete structure.
[0004] The technical solution adopted by the present invention is as follows: A method for preparing a graphene-enhanced copper carbide electrical contact material, comprising the following steps:
[0005] S1. Mixing: Mix copper powder with a particle size of 10-100 microns and carbide powder with a particle size of 0.5-5 microns according to the mass.
[0006] Mixing ratio 4:1 to 19:1;
[0007] S2, ball milling: high-energy ball milling of the mixed powder to evenly distribute the carbide reinforcement phase in the copper matrix;
[0008] S3, diffusion annealing-chemical vapor deposition: the ball-milled composite powder is loaded into the chemical vapor deposition furnace, first
[0009] Vacuum argon gas is filled to increase the temperature for diffusion annealing, and then methane and hydrogen are introduced to increase the temperature to achieve graphene growth on the surface of copper powder;
[0010] S4, pressing: pressing the powder processed in the previous step by cold isostatic pressing to obtain a blank;
[0011] S5, sintering: sintering the pressed blank and keeping it warm;
[0012] S6. Hot extrusion: The sintered blank is hot extruded to finally obtain the electrical contact material.
[0013] Furthermore, the carbide in step S1 is one or a mixture of tungsten carbide, titanium carbide, molybdenum carbide, silicon carbide, chromium carbide, tantalum carbide, niobium carbide, vanadium carbide or zirconium carbide.
[0014] Furthermore, in step S2, the mixed powder is subjected to high-energy ball milling, with a ball-to-material ratio of 10-20:1, a ball milling time of 4-24 hours, a rotation speed of 300-1000 rpm, and anhydrous ethanol is used as a protective medium, with a mass ratio of anhydrous ethanol to the mixed powder of 1:1-3.
[0015] Furthermore, in step S3, argon gas is introduced after vacuuming, and the temperature is raised to 500-700°C at a heating rate of 3-5°C / min, and kept warm for 2-4 hours; the introduction of argon gas is turned off, methane and hydrogen are introduced into the chemical vapor deposition furnace, and the temperature is raised to 800-1080°C at a heating rate of 10-15°C / min, and kept warm for 1-2 hours, wherein the flow rate of methane is 8-100sccm, and the flow rate of hydrogen is 10-100sccm.
[0016] Furthermore, in step S4, cold isostatic pressing is performed with a pressure of 250-400 MPa and a holding pressure of 30-60 seconds.
[0017] Furthermore, in step S5, the sintering temperature is 900-1050° C., and the holding time is 2-4 hours.
[0018] Furthermore, in step S6, the hot extrusion temperature is 750-1000° C., and the extrusion ratio is 30-100.
[0019] Advantages and beneficial effects of the present invention: The present invention uses high-energy ball milling to evenly distribute the carbide reinforcement phase in the copper matrix. Due to the effect of high-energy ball milling, the powder will be hardened and a large stress will be introduced inside, so that the copper atoms have a higher diffusion activity. Sufficient diffusion annealing at a suitable temperature can eliminate the inevitable small amount of oxidation during the ball milling process on the one hand; more importantly, it can make the copper atoms diffuse to the boundary of the composite powder to form a powder structure with a copper film; the subsequent high-temperature gas carbon source will catalyze nucleation and growth on the surface of the copper powder to form a single-layer or few-layer graphene film with few defects and complete structure. At the same time, due to the presence of carbides, the sintering of the composite powder during the chemical vapor deposition process is prevented, which is beneficial to the subsequent product processing. The preparation method of the present invention has the advantages of simple process and suitability for large-scale production, provides a new solution for the field of electrical materials, and has broad application prospects. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0021] Embodiment 1:
[0022] A method for preparing a graphene-enhanced copper carbide electrical contact material, comprising the following steps:
[0023] Step 1, mixing: copper powder and tungsten carbide powder are mixed in a mass ratio of 4:1, the average particle size of the copper powder is 74 microns, and the average particle size of the tungsten carbide is 1 micron.
[0024] Step 2, ball milling: the mixed powder is subjected to high-energy ball milling, the ball-to-material ratio is 10:1, the ball milling time is 4 hours, the rotation speed is 300 rpm, anhydrous ethanol is used as the protective medium, and the mass ratio of anhydrous ethanol to the mixed powder is 1:1.
[0025] Step 3, diffusion annealing-chemical vapor deposition: the ball-milled powder is loaded into a chemical vapor deposition furnace.
[0026] After evacuation, argon gas was injected, and the temperature was raised to 700°C at a rate of 3°C / min and kept at this temperature for 2 hours;
[0027] The argon gas was turned off, and methane and hydrogen were introduced into the chemical vapor deposition furnace. The temperature was raised to 800°C at a heating rate of 10°C / min and kept at that temperature for 2 hours. The flow rate of methane was 8sccm and the flow rate of hydrogen was 10sccm to complete the growth of graphene on the surface of the copper substrate.
[0028] Step 4: Pressing: The powder processed in step 3 is pressed by cold isostatic pressing at a pressure of 250 MPa.
[0029] Maintain pressure for 30 seconds.
[0030] Step 5, sintering: sinter the pressed blank at a temperature of 900°C for 2 hours;
[0031] Step 6, hot extrusion: hot extrusion the sintered billet at an extrusion temperature of 750°C and an extrusion ratio of 30.
[0032] The copper tungsten carbide 20 graphene 0.05 material prepared in this embodiment has a hardness (HV) of 168 and a fusion welding force of 48N, while the copper tungsten carbide 20 without graphene has a hardness (HV) of only 145 and a fusion welding force of 70N, indicating that the copper tungsten carbide 20 contact material without graphene is more likely to undergo fusion welding.
[0033] Example 2
[0034] A method for preparing a graphene-enhanced copper carbide electrical contact material, comprising the following steps:
[0035] Step 1, mixing: copper powder and titanium carbide powder are mixed at a mass ratio of 19:1. The average particle size of the copper powder is 100 microns, and the average particle size of the titanium carbide is 0.7 microns.
[0036] Step 2, ball milling: the mixed powder is subjected to high-energy ball milling, the ball-to-material ratio is 20:1, the ball milling time is 24 hours, the rotation speed is 1000 rpm, anhydrous ethanol is used as a protective medium, and the mass ratio of anhydrous ethanol to the mixed powder is 1:3.
[0037] Step 3, diffusion annealing-chemical vapor deposition: the ball-milled powder is loaded into a chemical vapor deposition furnace.
[0038] After evacuating the vacuum, argon gas was introduced, and the temperature was raised to 500°C at a heating rate of 5°C / min and kept warm for 4 hours. The argon gas was turned off, and methane and hydrogen were introduced into the chemical vapor deposition furnace, and the temperature was raised to 1080 degrees at a heating rate of 13°C / min, and kept warm for 2 hours. The flow rate of methane was 40sccm and the flow rate of hydrogen was 60sccm, to complete the growth of graphene on the surface of the copper substrate.
[0039] Step 4: Pressing: The powder processed in step 3 is pressed by cold isostatic pressing at a pressure of 400 MPa.
[0040] Maintain pressure for 50 seconds.
[0041] Step 5, sintering: sinter the pressed blank at a sintering temperature of 1050°C for 4 hours;
[0042] Step 6, hot extrusion: hot extrusion the sintered billet at an extrusion temperature of 900°C and an extrusion ratio of 100.
[0043] The copper titanium carbide 5 graphene 0.2 material prepared in this embodiment has a hardness (HV) of 141 and a welding force of 21N, while the copper titanium carbide 5 without graphene has a hardness (HV) of only 135 and a welding force of 50N, indicating that the copper titanium carbide 5 contact material without graphene has a higher probability of welding.
[0044] Example 3
[0045] A method for preparing a graphene-enhanced copper carbide electrical contact material, comprising the following steps:
[0046] Step 1, mixing: copper powder is mixed with molybdenum carbide powder and chromium carbide in a mass ratio of 90:4:6.
[0047] The average particle size of copper powder is 45 microns, the average particle size of molybdenum carbide is 2 microns, and the average particle size of chromium carbide is 3 microns.
[0048] Step 2, ball milling: the mixed powder is subjected to high-energy ball milling, the ball-to-material ratio is 15:1, the ball milling time is 12 hours, the rotation speed is 1000 rpm, anhydrous ethanol is used as a protective medium, and the mass ratio of anhydrous ethanol to the mixed powder is 1:3.
[0049] Step 3, diffusion annealing-chemical vapor deposition: the ball-milled powder is loaded into a chemical vapor deposition furnace.
[0050] After evacuation, argon gas was injected, and the temperature was raised to 600°C at a rate of 4°C / min and kept at this temperature for 3 hours;
[0051] The argon gas was turned off, and methane and hydrogen were introduced into the chemical vapor deposition furnace. The temperature was raised to 950 degrees at a heating rate of 12 degrees / min and kept warm for 2 hours. The flow rate of methane was 100 sccm and the flow rate of hydrogen was 100 sccm to complete the growth of graphene on the surface of the copper substrate.
[0052] Step 4: Pressing: The powder processed in step 3 is pressed by cold isostatic pressing at a pressure of 300 MPa.
[0053] Maintain pressure for 60 seconds.
[0054] Step 5, sintering: sinter the pressed blank at a sintering temperature of 1050°C for 3 hours;
[0055] Step 6: Hot extrusion: hot extrude the sintered billet at an extrusion temperature of 1000°C and an extrusion ratio of 66.
[0056] The copper molybdenum carbide 4 chromium carbide 6 graphene 0.1 material prepared in this embodiment has a hardness (HV) of 170 and a fusion welding force of 18N, while the copper molybdenum carbide 4 chromium carbide 6 without graphene has a hardness (HV) of only 156 and a fusion welding force of 46N, indicating that the copper molybdenum carbide 4 chromium carbide 6 contact material without graphene has a higher probability of fusion welding. Example 4:
[0057] A method for preparing a graphene-enhanced copper carbide electrical contact material, comprising the following steps:
[0058] Step 1, mixing: copper powder is mixed with silicon carbide, vanadium carbide and tantalum carbide powder in a mass ratio of 17:1:1:1, the average particle size of the copper powder is 74 microns, and the average particle size of the silicon carbide, vanadium carbide and tantalum carbide powder is 0.9 microns.
[0059] Step 2, ball milling: the mixed powder is subjected to high-energy ball milling, the ball-to-material ratio is 10:1, the ball milling time is 3 hours, the rotation speed is 500 rpm, anhydrous ethanol is used as the protective medium, and the mass ratio of anhydrous ethanol to the mixed powder is 1:2.
[0060] Step 3, diffusion annealing-chemical vapor deposition: the ball-milled powder is loaded into a chemical vapor deposition furnace.
[0061] After vacuuming, argon gas was injected, and the temperature was raised to 700°C at a rate of 3°C / min, and kept warm for 2 hours; the argon gas was turned off, and methane and hydrogen were introduced into the chemical vapor deposition furnace, and the temperature was raised to 950°C at a rate of 12 degrees / min, and kept warm for 2 hours to achieve the growth of graphene on the copper-based finished product, wherein,
[0062] The flow rate of methane is 40 sccm, and the flow rate of hydrogen is 40 sccm, which completes the growth of graphene on the surface of the copper substrate.
[0063] Step 4: Pressing: The powder processed in step 3 is pressed by cold isostatic pressing at a pressure of 300 MPa.
[0064] Maintain pressure for 30 seconds.
[0065] Step 5, sintering: sinter the pressed blank at a temperature of 950°C for 3 hours;
[0066] Step 6, hot extrusion: hot extrusion the sintered billet at an extrusion temperature of 100°C and an extrusion ratio of 50.
[0067] The copper silicon carbide 5 vanadium carbide 5 tantalum carbide 5 graphene 0.1 material prepared in this embodiment has a hardness (HV) of 190 and a fusion welding force of 12N, while the copper silicon carbide 5 vanadium carbide 5 tantalum carbide 5 without graphene has a hardness (HV) of only 167 and a fusion welding force of 43N, indicating that the copper silicon carbide 5 vanadium carbide 5 tantalum carbide 5 contact material without graphene is more likely to undergo fusion welding.
Claims
1. A method for preparing a graphene-enhanced copper carbide electrical contact material, comprising the following steps: S1. Mixing: copper powder with a particle size of 10-100 microns and carbide powder with a particle size of 0.5-5 microns are mixed in a mass ratio of 4:1 to 19:1; S2, ball milling: high-energy ball milling of the mixed powder to evenly distribute the carbide reinforcement phase in the copper matrix; S3, diffusion annealing-chemical vapor deposition: the ball-milled composite powder is loaded into a chemical vapor deposition furnace, first evacuated and filled with argon to increase the temperature for diffusion annealing, and then methane and hydrogen are introduced to increase the temperature to grow graphene on the copper powder surface; S4, pressing: pressing the powder processed in the previous step by cold isostatic pressing to obtain a blank; S5, sintering: sintering the pressed blank and keeping it warm; S6. Hot extrusion: The sintered blank is hot extruded to finally obtain the electrical contact material.
2. The method for preparing a graphene-enhanced copper carbide electrical contact material according to claim 1, characterized in that: The carbide in step S1 is one or a mixture of tungsten carbide, titanium carbide, molybdenum carbide, silicon carbide, chromium carbide, tantalum carbide, niobium carbide, vanadium carbide or zirconium carbide.
3. The method for preparing a graphene-enhanced copper carbide electrical contact material according to claim 2, characterized in that: In step S2, the mixed powder is subjected to high-energy ball milling, the ball-to-material ratio is 10-20:1, the ball milling time is 4-24 hours, the rotation speed is 300-1000 rpm, anhydrous ethanol is used as the protective medium, and the mass ratio of anhydrous ethanol to the mixed powder is 1:1-3.
4. The method for preparing a graphene-enhanced copper carbide electrical contact material according to claim 3, characterized in that: In step S3, after evacuation, argon gas is injected, and the temperature is raised to 500-700°C at a heating rate of 3-5°C / min, and kept warm for 2-4 hours; the argon gas is turned off, methane and hydrogen are introduced into the chemical vapor deposition furnace, and the temperature is raised to 800-1080°C at a heating rate of 10-15°C / min, and kept warm for 1-2 hours, wherein the flow rate of methane is 8-100sccm and the flow rate of hydrogen is 10-100sccm.
5. The method for preparing a graphene-enhanced copper carbide electrical contact material according to claim 4, characterized in that: In step S4, cold isostatic pressing is adopted, the pressure is 250-400 MPa, and the pressure is maintained for 30-60 seconds.
6. The method for preparing a graphene-enhanced copper carbide electrical contact material according to claim 5, characterized in that: In step S5, the sintering temperature is 900-1050° C., and the holding time is 2-4 hours.
7. The method for preparing a graphene-enhanced copper carbide electrical contact material according to claim 6, characterized in that: In step S6, the hot extrusion temperature is 750-1000° C., and the extrusion ratio is 30-100.